Novel Antidepressant-Like Activity of Propolis Extract Mediated by Enhanced Glucocorticoid Receptor Function in the Hippocampus. (18th June 2013) - Lee, Mi-Sook; Kim, Young Han; Park, Wan-Soon; Ahn, Won Gyeong; Park, Ok Kyu; Kwon, Seung-Hae; Morita, Kyoji; Shim, Insop; Her, Song
Abstract : Propolis is a natural product made by honeybees that has been widely used in folk medicine with a broad spectrum of biological activities. To investigate the antidepressant-like activity of propolis extract, CD-1 mice were administered an ethanol extract of propolis (50, 100, or 200 mg/kg, p.o.) prior to the behavioral test. The propolis extract-treated group showed a dose-dependent decrease in immobility time in the FST and tail suspension test without altering locomotor activity. Propolis extract decreased the limbic hypothalamic-pituitary-adrenal axis response to the FST as indicated by an attenuated corticosterone response and decreased in c-fos immunoreactive neurons in the hippocampal dentate gyrus. Western blot analysis revealed a reduction in hippocampal glucocorticoid receptor (GR) expression following the FST, which was reversed by propolis extract. Propolis extract also increased pGR(S220)/(S234) ratio by a differential phosphorylation in S220 and S234. FST-induced downregulation of cAMP-responsive element binding protein phosphorylation at S133 (pCREB) was restored by propolis extract, showing a strong and positive relationship between pCREB and pGR(S220)/(S234) ratio. These findings suggest that the propolis extract potentiates antidepressant-like activity by enhancing GR function which is one of the therapeutic mechanisms of antidepressant; thus, propolis extract may provide a novel therapy for depression.